A comparison of the agronomic management of a winter barley hybrid and a conventional genotype: effect of the seeding rate, soil tillage and nitrogen fertilization - Scapino, Mattia; Meloni, Raffaele; Blandino, Massimo (Frontiers in Agronomy, 2025)
In a context of climate change, barley can play a key role in cereal cropping systems, but the competitiveness of the crop requires the introduction of system innovations to increase its yield potential and to make the use of agronomic inputs more efficient. A hybrid genotype was compared with a conventional genotype in a three-year study. The treatments involved a factorial comparison of four combinations of genotype per seed density (medium vs high seed rate for each genotype), two soil tillages (conventional CT vs minimum tillage MT) and two N fertilization (equally split between the tillering and stem elongation growth stages vs a higher rate at the stem elongation stage). The hybrid genotype showed a higher grain yield (+8%) than the conventional one, as a consequence of a higher stay green. The lower ear density of the hybrid (-20%) was compensated by a higher number of kernels per ear (+16%) and a higher grain weight (+14%). A higher seeding rate did not increase the ear density and the grain yield; furthermore, CT and a higher N fertilization at the tillering stage led to a more rapid crop establishment. An increase in the seeding rate and the more balanced N application between the proposed timings resulted in a higher test weight for the hybrid (+0.9 kg hL-1). The hybrid genotype had a lower grain protein content than the conventional one, although this parameter increased on average by 0.4% for CT and a higher N application at stem elongation; moreover, the hybrid genotype showed a higher susceptibility to deoxynivalenol contamination (+51%). As regard the modelled global warming potential, the higher grain yield of the hybrid led to lower greenhouse gases emissions (-9%), compared to the conventional genotype. The adoption of MT, which did not have any impact on barley productivity, compared to CT, resulted in a further reduction of the environmental impact (-21%). The introduction of hybrids combined with a correct adaptation of other crop practices could be a way of improving both the grain yield and sustainability of the cereal cropping system.